PERAN BAHASA ARAB DALAM PENDIDIKAN ISLAM SEBAGAI URGENSITAS MENGHADAPI REVOLUSI INDUSTRI 4.0 - Cahya Edi Setyawan; Khairul Anwar (Fakultas Tarbiyah Universitas Ibrahimy, 2020)
With the presence of the Industrial Revolution 4.0, it automatically influenced the process of scientific development in Islamic education and Arabic. the development is felt in the aspects of its objectives, teaching methodology, and learning media, and competency standards of graduates who have soft skills and hard skills. Arabic, which has always been considered less important for some learners, has become an